2017
DOI: 10.7203/ciriec-e.90.9201
|View full text |Cite
|
Sign up to set email alerts
|

Brakes and barriers of Corporate Volunteering

Abstract: The objective of this research is to study which are the determinants for the participation of employees in Corporate Volunteer actions -hereafter CV-that can become barriers and brakes, and which ones can mean negative consequences for the company. Ignorance of managers for these programs, about which are those brakes and its relevance, may be behind the low participation fees that companies have in their Corporate Volunteering Programs.For this purpose, we conducted a qualitative empirical study to define a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…For some authors, employee volunteering constitutes a dynamic global force carried out by companies that want to make a difference by altering how to deal with international and local problems (Allen 2003(Allen , 2011. Some authors (Santos and Fernández 2017) analyse how to involve employees in corporate volunteering programs, and for this, they study both the factors that influence their participation as well as their motivations, barriers and obstacles. Research "has largely demonstrated that employee volunteering is beneficial for both employees and companies" (Rodell et al 2016, p. 2).…”
Section: An Approach To the Definition Of Employee Volunteeringmentioning
confidence: 99%
See 1 more Smart Citation
“…For some authors, employee volunteering constitutes a dynamic global force carried out by companies that want to make a difference by altering how to deal with international and local problems (Allen 2003(Allen , 2011. Some authors (Santos and Fernández 2017) analyse how to involve employees in corporate volunteering programs, and for this, they study both the factors that influence their participation as well as their motivations, barriers and obstacles. Research "has largely demonstrated that employee volunteering is beneficial for both employees and companies" (Rodell et al 2016, p. 2).…”
Section: An Approach To the Definition Of Employee Volunteeringmentioning
confidence: 99%
“…On the other hand, "Corporate volunteerism is a way for employees to actively become part of the CSR activity in the organization" (Caligiuri et al 2013). However, the critical barrier for employees is the lack of time and other aspects related to the scarcity of resources, the lack of support from management or not considering the employees' motivations and needs (Santos and Fernández 2017). Furthermore, some studies find that employees feel that if they carry out corporate volunteering activities during working hours, when they return to their position, they have to make up the hours dedicated to the initiative, and also, other employees can see that the time that other employees dedicate to volunteer activities implies an increased workload for them, with consequent discomfort among other colleagues (Santos and Fernández 2017).…”
Section: An Approach To the Definition Of Employee Volunteeringmentioning
confidence: 99%